2012
DOI: 10.1055/s-0032-1326987
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Changes during Pregnancy: Impact of Race, Body Mass Index, and Weight Gain

Abstract: Objective To investigate the effect of race, body mass index (BMI), and weight gain on blood pressure in pregnancy and postpartum. Study Design Secondary analysis of pregnant women aged 14 to 25 who received prenatal care at a university-affiliated public clinic in New Haven, Connecticut and delivered singleton term infants (n = 418). Longitudinal multivariate analysis was used to evaluate blood pressure trajectories from pregnancy through 12 weeks postpartum. Results Obese and overweight women had signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
4
10
0
Order By: Relevance
“…[2, 57] Moreover, in our study and in a similar cohort these differences remained stable over time. [2] Two other studies reported that these differences decreased slightly over time, as normal weight women had a more rapid increase in BP at the end of pregnancy compared to overweight and obese women.…”
Section: Discussionsupporting
confidence: 68%
“…[2, 57] Moreover, in our study and in a similar cohort these differences remained stable over time. [2] Two other studies reported that these differences decreased slightly over time, as normal weight women had a more rapid increase in BP at the end of pregnancy compared to overweight and obese women.…”
Section: Discussionsupporting
confidence: 68%
“…In our study, we had the ability to adjust for several important confounders, such as maternal age, smoking, early pregnancy BMI, and diabetes mellitus. 39,40 However, we did not have data on weight gain during pregnancy, which can affect blood pressure trajectories during pregnancy 39 and also the association with SGA. 41 Nor we had data on maternal ethnicity, which can affect both blood pressure trajectories during pregnancy and our outcomes.…”
Section: Strengths and Limitationsmentioning
confidence: 96%
“…41 Nor we had data on maternal ethnicity, which can affect both blood pressure trajectories during pregnancy and our outcomes. 39,42,43 Blood pressure measurements were collected during routine antenatal appointments by midwifes, and the measurements can, therefore, have inherent and interobserver variability. This would, however, only expect to introduce random rather than systemic error.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Women with a high body mass index (BMI) are more likely to have pregnancy complications and adverse maternal and perinatal outcomes including gestational diabetes (Hedderson et al, 2012; Solomon et al, 1997), pre-eclampsia (Baeten et al, 2001; Bodnar et al, 2005), high blood pressure (Magriples et al, 2013), placental dysfunction (Hastie and Lappas, 2014; Higgins et al, 2013), preterm births (Cnattingius et al, 2013; Wang et al, 2011), and infants born either large or small for gestational age (Djelantik et al, 2012). The prevalence of neurodevelopmental disorders have increased dramatically in parallel with the rise in obesity rates (Boyle et al, 2011; Elsabbagh et al, 2012; Fombonne, 2011), leading researchers to examine the impact of maternal obesity, weight gain during pregnancy, and prenatal diet on offspring behavior.…”
Section: Introductionmentioning
confidence: 99%